INFORMATION TECHNOLOGIES IN SYSTEM OF CUSTOMER RELATIONSHIP MANAGEMENT - VOLOBOY, Anastasia; MOKRA, Anna; BЕLOZERTSEV, Vasyl; YELISYEYEVA, Oxana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In article CRM systems are analyzed. The concept and principles of their work are presented. Process of introduction of CRM systems is analyzed. In addition, the article presents the concept of CRM-system.In modern business, the need to automate various processes has become commonplace. It is becoming increasingly difficult to keep warehousing or accounting without the use of specialized software. Sales representatives use special programs to place and send orders to the office via tablet or mobile phone, quite a large number of orders come from the site in the form of ready-to-process documents. However, customer relationships, especially in small and medium-sized businesses, are often conducted without the introduction of automation and sufficient attention to accounting. At the same time, each sales manager works as he sees fit, records calls, other types of interaction with customers at his own discretion, or refuses to record at all. way out of this situation - automation and standardization of customer relationship management, i.e. the introduction of CRM-system.Customer Relationship Management (CRM) is software that helps you successfully monitor, organize, and schedule customer service. CRM-systems help sales departments by telling managers what to do: respond to a new request, call the customer, plan the transaction. Robots themselves send emails and text messages to customers when the application is in the desired status, automatically launch ads and more. CRM allows you to not lose orders from new customers, systematize the work of managers and control it, find points for optimization and further growth of the company. CRM system standardizes and automates processes in the sales department.
Keywords: CRM systems; classification; construction principles; information technologies